ANALYSIS OF QRIS USER EXPERIENCE USING THE USER EXPERIENCE QUESTIONNAIRE (UEQ) METHOD - Tira Siya Fajar Rahayu; Muhammad Fikry Aransyah (Fakultas Teknik Universitas Lambung Mangkurat, 2023)
Digital wallets are the most preferred payment method by Indonesian digital society compared to other payment methods, namely cash payments and bank transfers. Over time, several digital wallet platforms began to create QR codes according to their respective platforms. With each platform having its own QR Code, this can make it difficult for users to make payments. Therefore, Bank Indonesia, which is tasked with regulating and maintaining the smooth running of the payment system, regulates the QR Code to be standardized in accordance with the International Europe Mastercard Visa standard. A product is said to be successful if the product is able to meet user needs to increase user satisfaction. In order for the product to meet the standards, it is necessary to evaluate the quality of the product. One of the evaluations that must be carried out is an evaluation of the User Experience. The sampling technique used is purposive sampling with the criteria that domiciled in Samarinda and has used QRIS as a payment system. Data analysis was carried out using the UEQ Data Analysis Tool. The results of this study are that user experience (attractiveness, perspicuity, efficiency, dependability, stimulation, novelty) has a positive impression on QRIS user satisfaction in Samarinda City.